[PP.16.04] CIRCADIAN BLOOD PRESSURE PROFILE, INFLAMMATORY MARKERS AND EPICARDIAL FAT THICKNESS IN HYPERTENSIVE PATIENTS. (September 2016) - Tilea, I.; Hutanu, A.; Voidazan, S.; Puiac, C.I.; Varga, A.
Abstract : Objective: Circadian blood pressure profile is a very important marker in long-term management of hypertensive patients. Epicardial fat tissue may represent a direct cardiovascular risk marker unrelated to obesity. We aimed to investigate the association of inflammation markers and epicardial fat thickness (EFT), in hypertensive patients with high risk circadian blood pressure (BP) profile. Design and method: 45 hypertensive patients with a mean age of 60 ± 12.30 years were evaluated. All patients underwent 24-hour ambulatory BP monitoring (ABPM), epicardial fat tissue was measured using 2D echocardiography, and intima media thickness (IMT) was assessed. hs-CRP was evaluated for all patients. Circadian blood pressure profile was classified according to the ABPM; 22 (48.88%) patients with hypertension with a dipping pattern at night (dippers), 19 (42.22%) patients with hypertension with a non-dipping profile at night (non-dippers) and 4 (8.88%) hypertensive patients with reverse-dipper BP profile. Results: EFT of hypertensive patients was significantly higher in the non-dipper and reverse-dipper group, compared to the dipper, (non-dippers, 7.7 ± 2.6 mm; reverse-dipper, 6.8 ± 1.4 mm; dippers, 5.3 ± 1.9 mm; p < 0.001). When evaluating the inflammatory marker hs-CRP and EFT in hypertensive patients, there was a significantly correlation between increased EFT and hs-CRP in non-dippers and reverse-dippers. EFT and IMT in non-dipper and reverse-dipper hypertensive patients, showed a correlation between the presence of increased EFT (>6, 5 mm) and increased IMT with no correlation with BMI. EFT was also significantly correlated with 24-hour mean systolic BP and age. Conclusions: These findings suggest that visceral adiposity, particularly EFT, may be associated with vascular damage, independent of BMI, but related to the circadian hypertension profile. There was also an association between EFT and inflammation markers in non-dipper and reverse-dipper hypertensive patients. Visceral adiposity, particularly EFT, and a specific circadian BP profile associated with increased inflammatory markers may be used to indicate increased risk of hypertension-related adverse cardiovascular events.